(untitled) (TEST BioLaw Journal - Rivista di BioDiritto, 2020)
The pandemic emergency has changed our lives and our times. The fight against the new disease has unveiled several inequalities that significantly involve also gender issues. The aim of this essay is to develop some considerations regarding gender equality in health services during the pandemic. Particular attention is given both to organisation of health services and reproductive rights. The whole analysis is conducted under the perspective of time-factor, which proves to be determinant in the granting of both equality and fundamental rights. Conclusions suggest that this period shall be determinant for seriously tackling gender issues.